Perancangan Interior Kafe dengan Tema Adat Perkawinan di Kupang (NTT) - Adi Santosa, Arnold Simson Kabinani (Intra, 2014)
The At this time, the business cafe is one of many types of businesses that demand . One cafe that is being proliferated lately is that the concept of natural café. This type of segmentation Cafe has a diverse, ranging from the middle class to the upper class. One café that plays the middle market - lower is Cafe Design. Design Café has a target market of teenagers and college students, but it is possible to gain market share families, adults and the elderly. Accordance with menus, cafe interior design concept took a rustic feel combined with modern technology. Rustic interior style that is by presenting elements - natural elements of nature contain elements of local culture, so that every visitor that enters indirectly can also get to know the culture / customs in Kupang to just enjoy the atmosphere in the cafe, and the interior design is the design café rustic natural feel. interviews and literature studies.